AM PESANTREN DAN PEMBENTUKAN SPIRIT TOLERANSI - Mahfudz, Ahmad Mahfudz (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2020)
Tolerance is the most important part in the effort to uphold the national and state togetherness values. As a result of the loss of the spirit of tolerance, problems after problems occur in this country including the increasing radicalization of religion so that terrorism appears. In this case, Islam is accused of being an intolerant religion. It is truly an unfounded accusation because Islam itself is a religion which upholds the values of tolerance as stated in Surah al- Kafirun. To prevent this misunderstanding, Islamic boarding schools have become an important part of Islamic education institutions to be pioneers in providing intensive understanding to the community and especially to students about tolerance in all matters including religious tolerance. From that, the kiai as the caretakers of the Islamic boarding school must take the lead in providing an understanding of the meaning of tolerance and being an example to their students. As has been done by kiai Ahmad Ghazali Salim, M. HI. at the Darul Lughah Waddirasatil Islamiyah Islamic boarding school, Akkor Palengaan Pamekasan. Besides emphasizing the position of students in. Tolerating, he also became an example in applying the meaning of tolerance. Hopefully what he does can be an inspiration for other Islamic boarding schools in order to form the security and tranquility of religion in religious life.